Principles of fin and flipper locomotion on granular media - Mazouchova, Nicole (Georgia Institute of Technology, 2013)
Locomotion of animals, whether by running, flying, swimming or crawling, is crucial to their survival. The natural environments they encounter are complex containing fluid, solid or yielding substrates. These environments are often uneven and inclined, which can lead to slipping during footsteps presenting great locomotor challenges. Many animals have specialized appendages for locomotion allowing them to adapt to their environmental conditions. Aquatically adapted animals have fins and flippers to swim through the water, however, some species use their paddle-like appendages to walk on yielding terrestrial substrates like the beach. Beach sand, a granular medium, behaves like a solid or a fluid when stress is applied. Principles of legged locomotion on yielding substrates remain poorly understood, largely due to the lack of fundamental understanding of the complex interactions of body/limbs with these substrates on the level of the Navier-Stokes Equations for fluids. Understanding of the limb-ground interactions of aquatic animals that utilize terrestrial environments can be applied to the ecology and conservation of these species, as well as enhance construction of man-made devices. In this dissertation, we studied the locomotion of hatchling loggerhead sea turtles on granular media integrating biological, robotic, and physics studies to discover principles that govern fin and flipper locomotion on flowing/yielding media. Hatchlings in the field modified their limb use depending on substrate compaction. On soft sand they bent their wrist to utilize the solid features of sand, whereas on hard ground they used a rigid flipper and claw to clasp asperities during forward motion. A sea turtle inspired physical model in the laboratory was used to test detailed kinematics of fin and flipper locomotion on granular media. Coupling of adequate step distance, body lift and thrust generation allowed the robot to move successfully forward avoiding previously disturbed ground. A flat paddle intruder was used to imitate the animal's flipper in physics drag experiments to measure the forces during intrusion and thrust generation.